Tracing microbial community across endophyte-to-saprotroph continuum of Cinnamomum camphora (L.) Presl leaves considering priority effect of endophyte on litter decomposition - Xiao, Jiamin; He, Zaihua; He, Xingbing; Lin, Yonghui; Kong, Xiangshi (Frontiers in Microbiology, 2025)
Endophytes typically coexist with plants in symbiosis and transition into the saprobic system as plant tissues senesce, participating in the decomposition process of litter. However, the dynamic changes of endophytic communities during this process and their role in litter decomposition remain unclear. This study tracked the microbial composition across the transition from live leaves to litter in Cinnamomum camphora (L.) Presl (C. camphora), evaluating the contribution of endophytes to litter decomposition by examining microbial diversity, community assembly, and co-occurrence networks along the endophyte-to-saprotroph spectrum. The results revealed increasing bacterial diversity but stable fungal diversity, and the diversity of endogenous microbes is mirrored this in the saprophytic phase. Bacterial community assembly was characterized by deterministic processes during the symbiotic phase, shifted to stochastic processes during the saprophytic phase. In contrast, fungal community assembly was predominantly driven by stochastic processes throughout the continuum. Out of the 49 keystone taxa identified, only Pseudorhodoplanes sinuspersici demonstrated a significant positive correlation with community assembly. All identified bacterial keystone taxa during the saprophytic phase originated from endophytic sources, and around 80% of the fungal keystone taxa in the initial stages of decomposition were similarly endophytic in origin. Additionally, 60% of the dominant bacterial taxa and 28% of the dominant fungal taxa at the commencement of decomposition were of endophytic descent. This suggests that endogenous microbes possess the potential to evolve into both keystone and dominant taxa during the saprophytic phase. Endogenous keystone and dominant microbes both exhibited significant correlations with microbial network, indicating their substantial ecological presence in microbial community. Both endogenous keystone and dominant taxa exerted significant potential influences on litter decomposition. Overall, during the saprophytic phase, endophytes are likely to influence the assemblage of microbial communities, the network structure, and decomposition-related functions. Specifically, it appears that bacterial endophytes may possess a greater adaptability to the decomposition processes of leaf litter compared to their fungal counterparts.